Systemic Gaps in Addressing Child Sexual Violence Through the Criminal Justice System - Konoras, Isyana Kurniasari; Mustofa, Muhammad; Susanti, Vinita (Technium Social Sciences Journal, 2026)
Sexual violence against children remains a serious crime that continues to face significant challenges in the law enforcement process, particularly at the regional level. This study aims to identify the Systemic Gaps in addressing Child Sexual Violence Through the criminal justice system cases in North Sulawesi. Employing a qualitative approach, the research utilizes in-depth interviews with offenders and representatives of victim assistance institutions. The findings reveal that despite the existence of robust legal frameworks—such as Law No. 35 of 2014, Law No. 11 of 2012, and Law No. 12 of 2022—implementation at the practical level remains problematic. Key issues include delayed investigation processes, limited recovery services for victims, low sensitivity of law enforcement officers toward child victims, and weak interagency coordination. This study highlights the urgency of strengthening the capacity of law enforcement personnel, improving trauma-informed victim support services, and ensuring integrated cross-sectoral collaboration to establish a more responsive, just, and child-centered criminal justice system.